Growth Of Freshwater Pomfret Fish (Collosoma macropumum) In A Recirculation System With A Horizontal Filter - Rafiah, Siti; Junaidi, Muhammad; Diniarti, Nanda (Program Studi Budidaya Perairan Universitas Mataram, 2024)
Fish farming is one of the activities to meet the food needs of the fisheries sector, one ofwhich is freshwater fish cultivation which gets very high economic value so that freshwaterpomfret fish from year to year increases. Although this fish is rarely consumed, freshwaterpomfret fish is a product that is quite in demand. The recirculation system is an applicationoption to control the quality of water that passes through a filter. This study aims to analyzethe growth of freshwater pomfret fish (Collosoma macropomum) in a recirculation system with a horizontal filter. This research was carried out for 50 days, at the Fish Production andReproduction Laboratory, University of Mataram using an experimental method using a Complete Design (RAL) consisting of 4 treatments and 3 replicates where there were 12 experimental units. The test parameters include growth rate (absolute length, specific length, absolute weight and specific weight), feed conversion ratio (FCR), survival (SR) and water quality. The data was analyzed using Analysis of Variance (ANOVA) and continued with the Duncan test. The results showed that the test parameters included growth rate (absolute length, specific length, absolute weight and specific weight), feed conversion ratio (FCR), survival (SR) and the best water quality were found in P3 with a growth rate (absolute length of 7 cm, specific length of 0.033 %/day, absolute weight of 24.5 grams and specific weight of 0.053%/day), feed conversion ratio (FCR) of 1.1, survival (SR) of 90% and water quality (temperature of 29-30 °C, Dissolved Oxygen (DO) of 3-6 mg/L and pH of 7-8).